The Complex Interplay Between Emotion Regulation and Work Rumination on Exhaustion - Geisler, Martin; Buratti, Sandra; Allwood, Carl Martin (Frontiers in Psychology, 2019)
This study examined the interplay between emotion regulation strategies (reappraisal and suppression) and work-related rumination (affective work rumination and detachment from work) on exhaustion. In all, 1,985 participants from three human service occupations (psychologists, teachers, and ministers) completed the web-based survey. The results showed that reappraisal and detachment from work had a negative relation to exhaustion, whereas the relation between suppression and affective work rumination to exhaustion were positively directed. Moreover, results of mediation analyses showed that the associations between emotion regulation strategies and exhaustion were mediated by work-ruminative tendencies. However, results of moderation analyses did not support that work-ruminative tendencies have a conditional effect (i.e., moderate) on the relationship between emotion regulation strategies and exhaustion. The results suggest that work-ruminative tendencies are best understood as a mediator of the emotion regulation strategies – exhaustion relationship. Thus, the study contribute to the understanding of the strategies (and combination of strategies) people use to reduce exhaustion by adding novel insights into the role of person characteristics in the recovery process. We discuss our results in relation to previous research, provide recommendations for future research, and note possible practical implications.